Offspring sex ratio increases with paternal reproductive success in a colony of southern elephant seals - Hassen Allegue; Christophe Guinet; Samantha C. Patrick; Cécile Ribout; Coraline Bichet; Olivier Lepais; Denis Réale (Marine Mammal Science, 2024)
In polygynous species, male reproductive success is often determined by their ability to dominate female harems. Harem‐holders sire a disproportionate number of offspring. Male dominance tends to correlate with age, but intense competition and early male mortality limit most males from achieving high social status. To maximize reproductive success despite low rank, offspring sex ratio adjustment may have evolved, favoring the sex with higher fitness. If traits influencing dominance are heritable and confer reproductive advantages, we expect fathers with higher reproductive success to produce more sons, as they are more likely to become dominant. In contrast, subordinate males with lower success may benefit from siring more daughters. We tested this hypothesis on a colony of southern elephant seals breeding on the Kerguelen Archipelago. We used genetic markers to link the paternity of 540 pups to 58 breeding males. We found that the probability of siring a son increases from 43% to 54% with paternal relative reproductive success, supporting the offspring sex ratio adjustment hypothesis. Given that various factors influence sex ratio in a population, future studies should tease apart these ecological processes (e.g., paternal dominance, maternal condition, local density, or adult sex ratio) and investigate how they interact with each other.

Adding a diversity of legumes to a crop decision-support system: Maintaining satisfactory accuracy while keeping the model simple - M. Bedu; L. Lefèvre; A. Dupont; P. Dubrulle; R. Reau; P. Debaeke; M. Guinet; M.-H. Jeuffroy; P. Maury; A. Schneider; C. Schoving; P. Thiébeau; et al. (European Journal of Agronomy, 2023)

From Settlers to Subspecies: Genetic Differentiation in Commerson’s Dolphins Between South America and the Kerguelen Islands - Sebastián Kraft; MJosé Pérez-Alvarez; Carlos Olavarría; Rodrigo Moraga; C. Scott Baker; Debbie Steel; Paul Tixier; Christophe Guinet; Amelia Viricel; Paul Brickle; Marina Costa; Enrique Crespo; et al. (Frontiers in Marine Science, 2021)
Commerson’s dolphins ( Cephalorhynchus commersonii ) are separated into the subspecies C. c. commersonii , found along southern South America (SA) and the Falkland Islands/Islas Malvinas (FI/IM), and C. c. kerguelenensis , restricted to the subantarctic Kerguelen Islands (KI). Following the dispersal model proposed for the genus, the latter is thought to have originated from SA after a long-distance dispersal event. To evaluate this biogeographic scenario, a distribution-wide, balanced sampling of mitochondrial DNA (mtDNA) control region sequences was designed. New tissue samples from southern Chile, Argentina, FI/IM, and KI were added to published sequences from SA and KI, for a total of 256 samples. Genetic diversity indices, genetic and phylogeographic structure, and migration rates were calculated. One haplotype was shared between subspecies, with which all haplotypes of C. c. kerguelenensis formed a distinct group in the haplotype network. A new haplotype for C. c. kerguelenensis is reported. Differentiation in haplotype frequencies was found among localities within the distribution of C. c. commersonii , yet the phylogeographic signal was only statistically significant between subspecies. Coalescent-based historical gene flow estimations indicated migration between the northern and southern portions of the species’ range in SA as well as between SA and the FI/IM, but not between these and the KI. The net nucleotide divergence between dolphins from SA and the FI/IM was lower than the recommended threshold value suggested for delimiting subspecies, unlike that found between C. c. commersonii and C. c. kerguelenensis . The results are consistent with the model of post-glacial colonization of KI by South American C. commersonii , followed by an ongoing divergence process and subspecies status. Thus, C. c. kerguelenensis may represent the most recent diversification step of Cephalorhynchus , where isolation from their source population is driving a process of incipient speciation.

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

An alternative method for correcting fluorescence quenching - L. Biermann; C. Guinet; M. Bester; A. Brierley; L. Boehme (Ocean Science, 2015)
Under high light intensity, phytoplankton protect their photosystems from bleaching through non-photochemical quenching processes. The consequence of this is suppression of fluorescence emission, which must be corrected when measuring in situ yield with fluorometers. We present data from the Southern Ocean, collected over five austral summers by 19 southern elephant seals tagged with fluorometers. Conventionally, fluorescence data collected during the day (quenched) were corrected using the limit of the mixed layer, assuming that phytoplankton are uniformly mixed from the surface to this depth. However, distinct deep fluorescence maxima were measured in approximately 30% of the night (unquenched) data. To account for the evidence that chlorophyll is not uniformly mixed in the upper layer, we propose correcting from the limit of the euphotic zone, defined as the depth at which photosynthetically available radiation is ~ 1% of the surface value. Mixed layer depth exceeded euphotic depth over 80% of the time. Under these conditions, quenching was corrected from the depth of the remotely derived euphotic zone Zeu, and compared with fluorescence corrected from the depth of the density-derived mixed layer. Deep fluorescence maxima were evident in only 10% of the day data when correcting from mixed layer depth. This was doubled to 21% when correcting from Zeu, more closely matching the unquenched (night) data. Furthermore, correcting from Zeu served to conserve non-uniform chlorophyll features found between the 1% light level and mixed layer depth.

Ontogeny of aquatic behaviours in Antarctic fur seal (Arctocephalus gazella) pups in relation to growth performances at Kerguelen Islands - C. Gastebois; M. Viviant; C. Guinet (Polar Biology, 2011)

Survival rate, abundance, and residency of long‐finned pilot whales in the Strait of Gibraltar - P. Verborgh; R. De Stephanis; S. Pérez; Y. Jaget; C. Barbraud; C. Guinet (Marine Mammal Science, 2009)
Long‐finned pilot whales in the Strait of Gibraltar are distributed over the main shipping routes. This exposes them to risks of collisions and probable acoustic and physical disturbance. This species is also the target of whale‐watching operations. The aim of this study was to estimate the annual population size, survival rate, and population growth rate of pilot whales occurring in the Strait and their inter‐annual variation using photo‐identification. A robust design was used to estimate all three parameters. A total of 10,784 individual pilot whale fins were photographed and analyzed. The population size estimation in summer ranged from a low of 147 individuals in 1999 to a high of 265 individuals in 2003. The annual population growth rate was estimated from mark recapture models to be 5.5%. The survival rate of adults was estimated at 0.982 (95% CI: 0.955–0.993). The same individuals have been observed between years. This suggests that this population is resident in the Strait, at least during summer. This study provides baseline knowledge prior to a predicted increase in shipping traffic throughout the main foraging area due to the opening in 2007 of a major shipping harbor along the Moroccan coast of the Strait.

Long-term social structure of long-finned pilot whales (Globicephala melas) in the Strait of Gibraltar - R. de Stephanis; P. Verborgh; S. Pérez; R. Esteban; L. Minvielle-Sebastia; C. Guinet (acta ethologica, 2008)

Diet of the social groups of long-finned pilot whales (Globicephala melas) in the Strait of Gibraltar - R. de Stephanis; S. García-Tíscar; P. Verborgh; R. Esteban-Pavo; S. Pérez; L. Minvielle-Sebastia; C. Guinet (Marine Biology, 2008)

Multiple origins of vagrant Subantarctic fur seals: a long journey to the Brazilian coast detected by molecular markers - Juliana Machado Ferreira; Larissa Rosa de Oliveira; Louise Wynen; Marthán N. Bester; Christophe Guinet; Nadia Moraes-Barros; Felipe Mello Martins; Mônica M. C. Muelbert; Ignacio B. Moreno; Salvatore Siciliano; Paulo Henrique Ott; João Stenghel Morgante (Polar Biology, 2008)

Fish prey of Antarctic fur seals Arctocephalus gazella at Ile de Croy, Kerguelen - Y. Cherel; C. Guinet; Y. Tremblay (Polar Biology, 1997)